Clot dissolution is better with ultrasound assisted thrombolysis for fresh clots with higher cholesterol content - Zhou, Yufeng (2013)
Tissue plasminogen activator (tPA) remains the only drug for recanalization in acute ischemic stroke, and the dose is determined by the patient's body-weight. Properties of the blood clot as well as ultrasound exposure might affect the thrombolysis outcome. In this study, clot was prepared by mixing horse blood with CaCl2 solution and cholesterin up to 1.0 mg/ml. To simulate the aging effect serum was replaced by fresh blood periodically. 225 IU/ml of tPA was used to initiate lysis. Clot was exposed to continuous 2 MHz transcranial Doppler ultrasound at acoustic intensity of 340 mW/cm2. The weight of the blood clot increased with its age (from 37.28±2.87 mg at 2 hrs to 51.56±5.34 mg at 10 hrs, p < 0.05). Although no difference between clot-cholesterol levels and thrombolysis with ultrasound or tPA alone was found, combination of these modalities induced significant lysis in the clots with cholesterol levels of more than 0.5 mg/ml (clot-weight reduced by 41.68±2.3%) as compared to clots with normal cholesterol (30.60±4.10%; p < 0.05). Altogether, sonothrombolysis seems to work better in fresh thrombi with high-cholesterol levels.